“GREEN ECONOMY” – THE FUTURE OF WORLD ECONOMY - Corina Gribincea; Alexandru Gribincea; Alexandru A. Gribincea (Ринкова економіка: сучасна теорія і практика управління)
The most dynamically growing trend in the modern world is the development of green economy as one of the main conditions for nature preservation and the environment for future generations. Having polluted the planet for many years, the world community has reached the point of no return in the process of developing resources, extracting raw materials, and accelerated urbanization of territories. Year after year, the resource base of the planet is being depleted, while the amount of environmentally-friendly energy production based on natural renewable components increases. The electric power complex is a highly intelligent, large-format logistics system that can adequately respond to changes in the given stability parameters, therefore it is the scientific and applied tools of modern logistics and supply chain management are most effectively applied in the electric power industry. The chosen topic is of particular relevance due to the increased social and economic importance of energy, as electricity today is one of the primary conditions for the normal existence of the society, a necessity that can already be equated to our natural needs.